High-dielectric polyimide film, preparation method thereof and film capacitor
By introducing a polar trans-cyclohexane structure into the polyimide molecular chain and adding carbon fiber-coated nanobarium titanate fibers to the polyamic acid solution, the low dielectric constant of the polyimide film and the difficulty of filling the material are solved. Dispersion problem, achieving thin film materials with high dielectric constant and high energy storage density.
Patent Information
- Application Number
- CN202411447502.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
The existing polyimide film has a low dielectric constant, which limits its application in the field of capacitors. It is easy to cause difficult to disperse the filler when adding ceramic filler, resulting in a decline in material performance.
A polar trans-cyclohexane structure is introduced into the polyimide molecular chain, and nanobarium titanate fibers coated with carbon fibers are added to the polyamic acid solution to increase the dielectric constant and energy storage density of the film.
By introducing the polar trans-cyclohexane structure and nano-barium titanate fibers, the dielectric constant and energy storage density of the polyimide film are significantly improved, solving the problems of low dielectric constant and difficult filler dispersion, and reducing the The added amount of filler improves the performance and cost-effectiveness of the material.
Smart Images

Figure CN119331285A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high dielectric polymer film materials, and in particular to a high dielectric polyimide film and a preparation method thereof, and a film capacitor. Background Art
[0002] As a capacitor for electrostatic energy storage, film capacitors have firmly occupied 50% of the global high-voltage capacitor market share with their performance advantages. Film capacitors have great applications in power systems, pulse power, automotive electronics, oil and gas exploration equipment, and avionics. Compared with ceramic capacitors, polymer film capacitors have attracted much attention due to their advantages such as light weight, low cost, good flexibility, high breakdown strength, high energy density, many charge and discharge cycles, and easy large-scale processing.
[0003] At present, biaxially oriented polypropylene (BOPP) film is the most common polymer capacitor film, but its dielectric constant of only 2.2 and low heat resistance temperature hinder its development. Therefore, it is of great practical significance to develop dielectric films with both high dielectric constant and excellent heat resistance. Polyimide (PI) refers to a polymer containing an imide ring on the main chain. Due to its excellent heat resistance and comprehensive properties, especially in the field of dielectric energy storage, it has great application prospects as a structural and functional material.
[0004] Although polyimide has excellent comprehensive performance, its dielectric constant is usually between 2.9 and 3.6, which limits its application as a capacitor film. In recent years, relevant research on the dielectric modification of polyimide has emerged in an endless stream. At present, there are two common methods for improving the dielectric properties of polyimide: one is to design and adjust the molecular structure of polyimide. For example, in the scheme disclosed in the Chinese patent with publication number CN 118546365A, a high polar group is introduced on the main chain of polyimide, or a group containing a large volume or a long molecular chain is introduced on the side chain. Another method is to add an inorganic ceramic filler with a high dielectric constant to optimize the dielectric properties of polyimide. However, it is easy to have the problem that the filler is difficult to disperse in the matrix, which leads to the generation of carrier traps inside the film, reducing the breakdown strength and service life, as well as the decline of mechanical properties. There are also many scholars who introduce conductive particles as fillers. The presence of the conductive network will cause a huge change in the dielectric constant of the material, but it also brings high dielectric loss and low breakdown strength. It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] In view of this, the present invention proposes a high dielectric polyimide film and a preparation method thereof, and a film capacitor, wherein a polar trans-cyclohexane structure is introduced into a polyimide molecular chain to improve the dielectric constant of the polyimide film.
[0006] The technical solution of the present invention is implemented as follows: The present invention provides a method for preparing a high dielectric polyimide film, the method comprising: obtaining a polyamic acid precursor solution, and subjecting the polyamic acid precursor solution to thermal imidization to form a film.
[0007] Wherein, the obtaining of the polyamic acid precursor solution comprises: reacting cyclohexanediamine or cyclohexanediamine salt with anhydride monomer to generate a polyamic acid solution.
[0008] More preferably, the cyclohexanediamine salt is trans-cyclohexanediamine acetate.
[0009] More preferably, the anhydride monomer is hexafluoroisopropylphthalic anhydride.
[0010] More preferably, the reaction of cyclohexanediamine or cyclohexanediamine salt with anhydride monomer comprises:
[0011] Dissolve cyclohexanediamine or cyclohexanediamine salt in a solvent and cool to 0-10°C;
[0012] At 0-10° C., anhydride monomers are added to the reaction solution in batches and reacted to obtain a polyamic acid solution.
[0013] On the basis of the above technical solution, preferably, the step of obtaining the polyamic acid precursor solution further comprises:
[0014] Adding nano-barium titanate fibers coated with carbon fibers into the polyamic acid solution to form the polyamic acid precursor solution;
[0015] In the polyamic acid precursor solution, the mass ratio of the nano-barium titanate fiber coated with the carbon fiber to the polyamic acid is between 1: (10-20).
[0016] More preferably, the nano-barium titanate fiber coated with carbon fiber is prepared by the following method:
[0017] Barium acetate and butyl titanate are reacted in a first solvent to form a spinnable barium titanate precursor solution;
[0018] dissolving the polyacrylonitrile spinning solution in a second solvent to form a polyacrylonitrile solution;
[0019] The coaxial fiber was prepared by using the coaxial spinning technology with the barium titanate precursor solution as the shell solution and the polyacrylonitrile solution as the core solution.
[0020] The coaxial fibers are calcined to obtain nano-barium titanate fibers coated with carbon fibers.
[0021] More preferably, the first solvent is a mixed solution of ethanol, acetic acid and deionized water; and the second solvent is N,N-dimethylacetamide.
[0022] On the basis of the above technical solution, preferably, the step of obtaining the polyamic acid precursor solution further comprises:
[0023] Adding nano-barium titanate fibers to the polyamic acid solution to form the polyamic acid precursor solution;
[0024] In the polyamic acid precursor solution, the mass ratio of nano-barium titanate fiber to polyamic acid is between 1: (10-20).
[0025] The present invention also provides a high dielectric polyimide film, which is prepared by the above method.
[0026] The present invention also provides a film capacitor, which comprises the high dielectric polyimide film.
[0027] The method for preparing the high dielectric polyimide film of the present invention has the following beneficial effects compared with the prior art:
[0028] 1. A high dielectric polyimide film with a higher dielectric constant is obtained by introducing a polar trans-cyclohexane structure into the polyimide molecular chain.
[0029] 2. During the preparation process, nano-barium titanate fibers coated with carbon fibers are added to the polyamic acid solution, so that polar groups (cyclohexane) and conductive particles (carbon fibers) are simultaneously present in the polyamic acid precursor solution, thereby obtaining a high dielectric polyimide film with a high dielectric constant and good energy storage density.
[0030] 3. The coexistence of polar groups and conductive particles reduces the amount of filler (nanobarium titanate fibers coated with carbon fibers), so that a high-dielectric polyimide film with good performance can be obtained by adding a small amount of filler. At the same time, the coating of carbon fibers by barium titanate also inhibits the negative impact of the formation of the conductive network, thereby reducing the influence of the conductive network on dielectric loss and breakdown strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 A schematic diagram showing comparison of dielectric constants of polyimide films at different test frequencies in some embodiments of the present invention;
[0033] Figure 2 This is a scanning electron microscope image of a fracture surface of a nano-barium titanate fiber coated with carbon fiber in an embodiment of the present invention;
[0034] Figure 3 Schematic diagram of comparison of dielectric constants of polyimide films at different test frequencies in some embodiments of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The embodiment of the present disclosure provides a method for preparing a high dielectric polyimide film, the method comprising: obtaining a polyamic acid precursor solution, and subjecting the polyamic acid precursor solution to thermal imidization to form a film.
[0037] Wherein, the obtaining of the polyamic acid precursor solution comprises: reacting cyclohexanediamine or cyclohexanediamine salt with anhydride monomer to generate a polyamic acid solution.
[0038] In this embodiment, by adding cyclohexanediamine or cyclohexanediamine salt, a polar cyclohexane structure is introduced into the polyamic acid molecular chain, so that the prepared polyimide film has a higher dielectric constant, thereby improving the application performance of the polyimide film.
[0039] In one embodiment of the present disclosure, the cyclohexanediamine salt is trans-cyclohexanediamine acetate.
[0040] In one embodiment of the present disclosure, the anhydride monomer is hexafluoroisopropylphthalic anhydride. The use of hexafluoroisopropylphthalic anhydride (6FDA) can improve the film-forming performance of the polyimide precursor solution.
[0041] In one embodiment of the present disclosure, the step of reacting cyclohexyldiamine or cyclohexyldiamine salt with an acid anhydride monomer comprises: dissolving cyclohexyldiamine or cyclohexyldiamine salt in a solvent and cooling the solvent to 0-10° C.;
[0042] At 0-10° C., anhydride monomers are added to the reaction solution in batches and reacted to obtain a polyamic acid solution.
[0043] In one embodiment of the present disclosure, the step of obtaining the polyamic acid precursor solution further comprises: adding nano-barium titanate fibers to the polyamic acid solution to form the polyamic acid precursor solution; in the polyamic acid precursor solution, the mass ratio of nano-barium titanate fibers to polyamic acid is between 1: (10-20). In this embodiment, nano-barium titanate fibers are added in a mass ratio of 1: (10-20) on the basis of adding cyclohexanediamine or cyclohexanediamine salt to the polyamic acid precursor solution. Barium titanate, as an inorganic ceramic filler, improves the dielectric properties of polyimide while reducing the impact on the breakdown strength of the film prepared using the precursor solution.
[0044] In one embodiment of the present disclosure, the obtaining of the polyamic acid precursor solution further comprises: adding nano-barium titanate fibers coated with carbon fibers to the polyamic acid solution to form the polyamic acid precursor solution;
[0045] In the polyamic acid precursor solution, the mass ratio of the nano-barium titanate fiber coated with the carbon fiber to the polyamic acid is between 1: (10-20).
[0046] In this embodiment, carbon fiber is added to the polyamic acid precursor solution as a conductive filler, and barium titanate is coated on the conductive filler. In this way, the conductive filler is used in combination with the inorganic ceramic filler, which reduces the amount of the inorganic ceramic filler and improves the dielectric properties of the polyimide film.
[0047] In one embodiment of the present disclosure, the nano-barium titanate fiber coated with carbon fiber is prepared by the following method: barium acetate and butyl titanate are reacted in a first solvent to form a spinnable barium titanate precursor solution; polyacrylonitrile spinning solution is dissolved in a second solvent to form a polyacrylonitrile solution; the barium titanate precursor solution is used as a shell solution and the polyacrylonitrile solution is used as a core solution to prepare coaxial fibers by coaxial spinning technology; the coaxial fibers are calcined to obtain nano-barium titanate fibers coated with carbon fiber. That is to say, the polyacrylonitrile solution is used as a core solution and the barium titanate precursor solution is used as a shell solution to obtain coaxial fibers by electrostatic spinning. After calcination, the polyacrylonitrile forms a carbon fiber inner core and the barium titanate forms an inorganic ceramic filler coated on the outside of the carbon fiber, thereby obtaining nano-barium titanate fibers coated with carbon fiber.
[0048] It is understandable that adding nano-barium titanate fibers coated with carbon fibers to the polyamic acid precursor solution can not only further improve the dielectric constant of the polyimide film, but also suppress the excessive dielectric loss and low breakdown strength caused by the formation of a conductive network through the coating of carbon fibers by barium titanate. In addition, because barium titanate is coated on the outside of the carbon fibers, the mass of the barium titanate inorganic ceramic filler is reduced under the same mass ratio conditions, thereby reducing the preparation cost of the polyimide film.
[0049] Exemplarily, the first solvent may be a mixed solution of ethanol, acetic acid, and deionized water; and the second solvent may be N,N-dimethylacetamide.
[0050] The properties of the high dielectric polyimide film prepared by the preparation method provided by the present disclosure are further illustrated by specific examples below.
[0051] Embodiment 1,
[0052] S1. Weigh 25 mmol of trans-cyclohexanediamine acetate and 25 mmol of hexafluoroisopropylphthalic anhydride (6FDA), place them in a vacuum drying oven at 60°C and dry them for 6 hours to remove water molecules to avoid the influence of water molecules on the degree of polymerization.
[0053] S2. In a nitrogen atmosphere, trans-cyclohexanediamine acetate was slowly added into a three-necked flask containing 80 ml of N,N-dimethylacetamide (DMAc), stirred for 0.5 h, and kept in an ice-water bath, and the water bath temperature was controlled below 8°C. Subsequently, 6FDA was added in batches every 0.5 h, for a total of four times. During the whole process, the solid content of the reaction system was controlled at 15% to 20%. After reacting for 6-10 h, a polyamic acid solution was obtained.
[0054] The chemical reaction in this step is as follows:
[0055]
[0056] S3, the prepared polyamic acid solution is formed into a film by solution casting and thermal imidization, and the temperature process is 150°C / 0.5h, 200°C / 0.5h, and 250°C / 0.5h, respectively. Then, it is naturally cooled to room temperature, and the peeled film is defined as a high dielectric polyimide film 1.
[0057] The chemical reaction in this step is as follows:
[0058]
[0059] Comparative Example 1
[0060] S1. Weigh 25 mmol of trans-cyclohexanediamine acetate and 25 mmol of pyromellitic dianhydride (PMDA), and then place them in a vacuum drying oven at 60° C. to dry for 6 h to remove water molecules to avoid the influence of water molecules on the degree of polymerization.
[0061] S2. In a nitrogen atmosphere, trans-cyclohexanediamine acetate was slowly added to a three-necked flask containing 80 ml of N,N-dimethylacetamide (DMAc), stirred for 0.5 h, and kept in an ice-water bath, and the water bath temperature was controlled below 8°C. PMDA was then added in batches every 0.5 h, for a total of four times. During the whole process, the solid content of the reaction system was controlled at 15% to 20%. After reacting for 6-10 h, a polyamic acid solution was obtained.
[0062] S3, forming a film from the polyamic acid solution by solution casting and thermal imidization, with the temperature process being 150°C / 0.5h, 200°C / 0.5h, and 250°C / 0.5h, and then naturally cooling to room temperature, and the peeled film is defined as polyimide film 1.
[0063] Comparative Example 2
[0064] S1. Weigh 25 mmol of trans-cyclohexanediamine acetate and 25 mmol of 2,3,3',4'-biphenyltetracarboxylic dianhydride (BPDA), and then place them in a vacuum drying oven at 60° C. to dry for 6 h to remove water molecules to prevent water molecules from affecting the degree of polymerization.
[0065] S2. In a nitrogen atmosphere, trans-cyclohexanediamine acetate was slowly added to a three-necked flask containing 80 ml of N,N-dimethylacetamide (DMAc), stirred for 0.5 h, and kept in an ice-water bath, and the water bath temperature was controlled below 8°C. Then BPDA was added in batches every 0.5 h, for a total of four times. During the whole process, the solid content of the reaction system was controlled at 15% to 20%. After reacting for 6-10 h, a polyamic acid solution was obtained.
[0066] S3, using solution casting method and thermal imidization to form a film, the temperature process is 150℃ / 0.5h, 200℃ / 0.5h, 250℃ / 0.5h, and then naturally cooled to room temperature, and the peeled film is defined as polyimide film 2.
[0067] Comparative Example 3
[0068] S1. Weigh 25 mmol of 4,4'-diaminodiphenyl ether (ODA) and hexafluoroisopropylphthalic anhydride (6FDA), and then place them in a vacuum drying oven at 60°C for 6 hours to remove water molecules to avoid the influence of water molecules on the degree of polymerization.
[0069] S2. In a nitrogen atmosphere, slowly add ODA into a three-necked flask containing 80 ml of N,N-dimethylacetamide (DMAc), stir for 0.5 h, and keep an ice-water bath to control the water bath temperature below 8°C. Then add 6FDA in batches every 0.5 h, for a total of four times. During the whole process, the solid content of the reaction system is controlled at 15% to 20%. After reacting for 6-10 h, a polyamic acid solution is obtained.
[0070] S3, using solution casting method and thermal imidization to form film, the temperature process is 150℃ / 0.5h, 200℃ / 0.5h, 250℃ / 0.5h. Then naturally cool to room temperature, the peeled film is defined as polyimide film 3.
[0071] Comparative Example 4
[0072] S1. Weigh 25 mmol of 4,4'-diaminodiphenyl ether (ODA) and 25 mmol of pyromellitic dianhydride (PMDA), and then place them in a vacuum drying oven at 60°C for 6 hours to remove water molecules to avoid the influence of water molecules on the degree of polymerization.
[0073] S2. In a nitrogen atmosphere, slowly add ODA into a three-necked flask containing 80 ml of N,N-dimethylacetamide (DMAc), stir for 0.5 h, and keep an ice-water bath, controlling the water bath temperature below 8°C. Then add PMDA in batches every 0.5 h, for a total of four times. During the whole process, the solid content of the reaction system is controlled at 15% to 20%. After reacting for 6-10 h, a polyamic acid solution is obtained.
[0074] S3, using solution casting method and thermal imidization to form film, the temperature process is 150℃ / 0.5h, 200℃ / 0.5h, 250℃ / 0.5h. Then naturally cool to room temperature, the peeled film is defined as polyimide film 4.
[0075] Comparative Example 5
[0076] S1. Weigh 25 mmol of 4,4'-diaminodiphenyl ether (ODA) and 25 mmol of 2,3,3',4'-biphenyltetracarboxylic dianhydride (BPDA), and then place them in a vacuum drying oven at 60°C for 6 hours to remove water molecules to avoid the influence of water molecules on the degree of polymerization.
[0077] S2. In a nitrogen atmosphere, slowly add ODA into a three-necked flask containing 80 ml of N,N-dimethylacetamide (DMAc), stir for 0.5 h, and keep an ice-water bath to control the water bath temperature below 8°C. Then add BPDA in batches every 0.5 h, for a total of four times. During the whole process, the solid content of the reaction system is controlled at 15% to 20%. After reacting for 6-10 h, a polyamic acid solution is obtained.
[0078] S3, forming a film from the polyamic acid solution by solution casting and thermal imidization, with the temperature process being 150°C / 0.5h, 200°C / 0.5h, and 250°C / 0.5h, and then naturally cooling to room temperature, and the peeled film is defined as polyimide film 5.
[0079] The high dielectric polyimide film 1 and polyimide films 2-5 were plated with silver electrodes using a magnetron sputtering instrument (polyimide film 1 was not formed into a film). The dielectric properties of the high dielectric polyimide film 1 and polyimide films 2-5 plated with silver electrodes were tested using an Agilent 4294A precision impedance analyzer at 150°C, and the dielectric constant (dielectric constant under relative vacuum conditions) was calculated, where ε0 is the vacuum dielectric constant, which is 8.854×10 -12 F / m, frequency test range is 40~1*10 6 Hz, the measurement results are shown in Table 1 (taking the frequency of 100 Hz as an example).
[0080] Table 1. Summary of polyimide film performance results
[0081] 100Hz Relative dielectric constant Film forming properties Example 1 8.89 Easy to form film without bubbles Comparative Example 1 No valid data Cannot form film, in powder form Comparative Example 2 7.29 Capable of forming film, but brittle Comparative Example 3 3.05 Easy to form film without bubbles Comparative Example 4 4.0 Capable of forming film, but brittle Comparative Example 5 4.7 Easy to form film without bubbles
[0082] Comparative Examples 1 and 2 are compared with Example 1, and the raw materials used are changed from hexafluoroisopropylphthalic anhydride to pyromellitic dianhydride (Comparative Example 1) or 2,3,3',4'-biphenyltetracarboxylic dianhydride (Comparative Example 2). It can be seen from the measurement results in Table 1 that the high dielectric polyimide film 1 has good film forming properties and a high dielectric constant.
[0083] Comparative Example 3 Compared with Example 1, the polyamic acid solution was prepared by using 4,4'-diaminodiphenyl ether (ODA) and hexafluoroisopropylphthalic anhydride. The polyimide film 3 finally obtained had good film-forming properties, but a low dielectric constant.
[0084] Comparative Example 4 is compared with Example 1. In the polyamic acid solution prepared by using 4,4'-diaminodiphenyl ether (ODA) and pyromellitic anhydride, the polyimide film 4 finally obtained is fragile after film formation and has a low dielectric constant.
[0085] Comparative Example 5 Compared with Example 1, the polyamic acid solution was prepared by using 4,4'-diaminodiphenyl ether and 2,3,3',4'-biphenyltetracarboxylic dianhydride. The polyimide film 5 finally obtained had good film-forming properties, but a low dielectric constant.
[0086] See also Figure 1 , which is a schematic diagram comparing the dielectric constants of the polyimide films prepared in Example 1 and Comparative Examples 2-5 at different test frequencies. Figure 1 It can be seen that, under the tested frequency, the dielectric constant of the polyimide film prepared in Example 1 is at a relatively high level.
[0087] Therefore, in the preparation method of the polyimide film provided by the present disclosure, the dielectric constant of the polyimide can be improved by introducing a trans-cyclohexane structure, and the film-forming properties of the polyimide can be improved by using hexafluoroisopropylphthalic anhydride (6FDA) as a synthetic monomer.
[0088] Example 2
[0089] S10, preparation of barium titanate sol by sol-gel method. Add ethanol, acetic acid, and deionized water (mass ratio of ethanol: acetic acid: deionized water = 10:9:1) into a beaker, stir for 1 min, then add 1.5 g of polyvinyl pyrrolidone (PVP) and 1.5 g of barium acetate, stir until the solid is completely dissolved; then add 2 g of butyl titanate, stir for 30 min, and let the solution stand until it is clear to obtain a spinnable barium titanate precursor solution, which is recorded as Sol A. Dissolve polyacrylonitrile (PAN) spinning solution in DMF (mass ratio of PAN:DMF = 1:9), which is recorded as Sol B.
[0090] S20, coaxial spinning to prepare coaxial fiber membrane, wherein the coaxial needle consists of an inner needle and an outer needle, the inner needle is a 22-gauge needle, and the outer needle is a 17-gauge needle. Sol A is connected to the outer needle as a shell solution, and Sol B is connected to the inner needle as a core solution. The electrospinning instrument is operated for 12 hours under the spinning conditions of a positive voltage of 10.5 kV, a negative voltage of 2.5 kV, a syringe thrust speed of 0.05 mm / min connected to the outer needle, and a syringe thrust speed of 0.03 mm / min connected to the inner needle. Subsequently, the barium titanate fiber membrane coated with PAN fiber is obtained by spinning, dried at 60°C for 12 hours to remove the solvent, and pre-oxidized at 300°C for 3 hours to maintain the fiber shape. Finally, under nitrogen protection, high-temperature calcination (heating rate 2°C / min, calcination conditions 900°C for 3 hours) is performed to obtain nano-barium titanate fibers coated with carbon fibers. As Figure 2 Shown is a scanning electron microscope image of the fracture surface of nano-barium titanate fiber coated with carbon fiber.
[0091] S30, weigh 0.1g of the nano-barium titanate fiber coated with carbon fiber in step S20, add about 1.5g of N-methylpyrrolidone (NMP), and stir ultrasonically for 1h to evenly disperse the fiber in the solution. Then add 10g of the polyamic acid solution prepared in step S2 of Example 1 and stir for 0.5h. The mixed solution is formed into a film by solution casting and thermal imidization, and the temperature process is 150℃ / 0.5h, 200℃ / 0.5h, and 250℃ / 0.5h. Then cool naturally to room temperature, and the peeled film is defined as a high dielectric polyimide composite film 1.
[0092] Example 3
[0093] S10, preparation of barium titanate sol by sol-gel method. Add ethanol, acetic acid, and deionized water (mass ratio of ethanol: acetic acid: deionized water = 10:9:1) into a beaker, stir for 1 min, then add 1.5 g of PVP and 1.5 g of barium acetate, stir until the solid is completely dissolved; then add 2 g of butyl titanate, stir for 30 min, and let the solution stand until it is clear to obtain a spinnable barium titanate precursor solution.
[0094] S20, electrospinning to prepare fiber membrane, using a single needle of model No. 19, the electrospinning instrument was operated for 8 hours under the spinning conditions of positive voltage of 12.5kV, negative voltage of 3.0kV, and needle-connected syringe propulsion speed of 0.15mm / min. The barium titanate fiber membrane obtained by spinning was dried at 60℃ for 12h to remove the solvent, and then calcined at high temperature (heating rate of 2℃ / min, calcination conditions of 800℃ for 3h) to obtain nano barium titanate fiber.
[0095] S30, weigh 0.1g of the prepared nano-barium titanate fiber, add about 1.5g of NMP, and stir ultrasonically for 1h to evenly disperse the fiber in the solution. Then add 10g of the polyamic acid solution prepared in step S2 of Example 1 and stir for 0.5h. The mixed solution is formed into a film by solution casting and thermal imidization, and the temperature process is 150℃ / 0.5h, 200℃ / 0.5h, and 250℃ / 0.5h. Then cool naturally to room temperature, and the peeled film is defined as a high dielectric polyimide composite film 2.
[0096] Silver electrodes were plated on the high dielectric polyimide composite film 1 and the high dielectric polyimide composite film 2 using a magnetron sputtering instrument. The dielectric properties of the high dielectric polyimide composite films 1 and 2 plated with silver electrodes and the high dielectric polyimide film 1 were tested at 150°C using an Agilent 4294A precision impedance analyzer to calculate the dielectric constant (relative dielectric constant under vacuum conditions) and dielectric loss. The frequency test range was 40 to 1*10 6 Hz.
[0097] The breakdown field strength of high dielectric polyimide composite films 1 and 2 and high dielectric polyimide film 1 was tested using a withstand voltage tester (CS2674AX, Allwin), and the breakdown field strength (E b ).
[0098] The energy storage density of high dielectric polyimide composite films 1 and 2 and high dielectric polyimide film 1 is calculated according to formula 1, where ε0 is the vacuum dielectric constant, which is 8.854×10 -12 F / m. The measurement results are shown in Table 2 (taking the frequency of 100 Hz as an example).
[0099] Formula 1:
[0100]
[0101] Table 2. Test results of film properties prepared in Examples 1-3
[0102]
[0103] Combination Figure 3 As shown in Table 2, compared with the high dielectric polyimide composite film 1 prepared in Example 1, the dielectric constant of the high dielectric polyimide composite film 2 prepared in Example 3 is increased from 8.89 to 20.15, and the energy storage density is also increased.
[0104] The high dielectric polyimide composite film 1 prepared in Example 2 is compared with the high dielectric polyimide film 1 prepared in Example 1, and the dielectric constant is increased from 8.89 to 39.48, and at the same time, the energy storage density is doubled. That is to say, by introducing a polar trans-cyclohexane structure on the polyamic acid molecular chain in the polyamic acid solution and adding hexafluoroisopropylphthalic anhydride, a polyimide film with good film-forming properties and high dielectric constant can be obtained. Further, adding nano-barium titanate fibers to the polyamic acid solution can further improve the dielectric constant of the polyimide film. Further, by adding nano-barium titanate fibers coated with carbon fibers to the polyamic acid solution, the dielectric constant and energy storage density of the obtained polyimide film can be further improved, thereby obtaining a dielectric material with a high dielectric constant and high energy storage density.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high dielectric polyimide film, characterized in that: include: Obtaining a polyamic acid precursor solution, and subjecting the polyamic acid precursor solution to thermal imidization to form a film; Wherein, the step of obtaining the polyamic acid precursor solution comprises: Cyclohexanediamine or cyclohexanediamine salt is reacted with anhydride monomer to generate a polyamic acid solution.
2. The method for preparing a high dielectric polyimide film according to claim 1, characterized in that: The cyclohexanediamine salt is trans-cyclohexanediamine acetate.
3. The method for preparing a high dielectric polyimide film according to claim 1 or 2, characterized in that: The acid anhydride monomer is hexafluoroisopropylphthalic anhydride.
4. The method for preparing a high dielectric polyimide film according to claim 1, characterized in that: The step of reacting cyclohexanediamine or cyclohexanediamine salt with anhydride monomer comprises: Dissolve cyclohexanediamine or cyclohexanediamine salt in a solvent and cool to 0-10°C; At 0-10° C., anhydride monomers are added to the reaction solution in batches and reacted to obtain a polyamic acid solution.
5. The method for preparing a high dielectric polyimide film according to claim 1, characterized in that: The obtaining of the polyamic acid precursor solution further comprises: Adding nano-barium titanate fibers coated with carbon fibers into the polyamic acid solution to form the polyamic acid precursor solution; In the polyamic acid precursor solution, the mass ratio of the nano-barium titanate fiber coated with the carbon fiber to the polyamic acid is between 1: (10-20).
6. The method for preparing a high dielectric polyimide film according to claim 5, characterized in that: The nano-barium titanate fiber coated with carbon fiber is prepared by the following method: Barium acetate and butyl titanate are reacted in a first solvent to form a spinnable barium titanate precursor solution; dissolving the polyacrylonitrile spinning solution in a second solvent to form a polyacrylonitrile solution; The coaxial fiber was prepared by using the coaxial spinning technology with the barium titanate precursor solution as the shell solution and the polyacrylonitrile solution as the core solution. The coaxial fibers are calcined to obtain nano-barium titanate fibers coated with carbon fibers.
7. The method for preparing a high dielectric polyimide film according to claim 6, characterized in that: The first solvent is a mixed solution of ethanol, acetic acid and deionized water; the second solvent is N,N-dimethylacetamide.
8. The method for preparing a high dielectric polyimide film according to claim 1, characterized in that: The obtaining of the polyamic acid precursor solution further comprises: Adding nano-barium titanate fibers to the polyamic acid solution to form the polyamic acid precursor solution; In the polyamic acid precursor solution, the mass ratio of nano-barium titanate fiber to polyamic acid is between 1: (10-20).
9. A high dielectric polyimide film, characterized in that: The high dielectric polyimide film is prepared by any one of the methods of claims 1 to 8.
10. A film capacitor, characterized in that: Comprising the high dielectric polyimide film as claimed in claim 9.
Citation Information
Patent Citations
High-dielectric polyimide film and preparation method thereof
CN118546365A